A framework for the adoption of lean thinking within public procurement. (1st October 2010) - Schiele, Joseph J.; McCue, Clifford P.
Public procurement is suffering from rule-driven processes, inefficient delivery systems and poor management of resources. Lean thinking, an approach centred on providing customers with exactly what they want, when they want it, may provide a means to address the problems associated with public procurement. A review of the extant literature, involving studies that span nearly every continent, provide strong support for these claims. The problems associated with public procurement, a distinction between lean production versus lean thinking, examples of how lean thinking has been successfully applied within the public sector, barriers to overcome, how to identify the procurement value stream, potential sources of waste, moving forward with rapid improvement events and how to achieve longer-term sustainable change are discussed. The purpose of this paper is two fold. First, to present in practical terms, how lean thinking can be applied so that some of the problems associated with public procurement can be overcome. Second, to provide an approach that could be used to address a number of questions suggested to guide future research.